Economic Growth, Technical Change Biases, and the Elasticity of Substitution: A Test of the De La Grandville Hypothesis - Yuhn, Ky-hyang (The Review of Economics and Statistics, 1991)
Ky-hyang Yuhn, Economic Growth, Technical Change Biases, and the Elasticity of Substitution: A Test of the De La Grandville Hypothesis, The Review of Economics and Statistics, Vol. 73, No. 2 (May, 1991), pp. 340-346